2021
DOI: 10.1080/14675986.2021.1893986
|View full text |Cite
|
Sign up to set email alerts
|

Exploring teachers’ perceptions and practices of intercultural education in an international school

Abstract: This article examines teachers' perceptions and experiences of intercultural education. The participants (n = 11) were teachers who work in the Primary Years Programme (PYP) of an International Baccalaureate (IB) school in the Netherlands. The school was chosen as the context for this study due to the emphasis on intercultural understanding in IB education. The data were collected through a closed and open-ended survey in 2019 and complemented by an ethnographical method. The results showed that the teachers m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
0
7
1
1
Order By: Relevance
“…They remind us, rightly, that working from beliefs and discourses may not reveal the complexities of how teachers engage concretely with diversity in classrooms and that their real practices might be more versatile depending on, for example, the context and access to resources. In a 2021 paper based on an international school in the Netherlands, the results of Roiha and Sommier (2021) differ somewhat from the previous study. Although in-service teachers all reported caring for and 'doing' intercultural education, their discourses on interculturality and diversity were limited to national cultures and traditions in class, with a few of them opening up to more critical views on interculturality beyond mere catalogues of culturalist perspectives, that is, solid and often stereotypical representations of national cultures (see Holliday, 2010).…”
Section: Teachers' Assumptions Beliefs Experiences and Practicescontrasting
confidence: 56%
“…They remind us, rightly, that working from beliefs and discourses may not reveal the complexities of how teachers engage concretely with diversity in classrooms and that their real practices might be more versatile depending on, for example, the context and access to resources. In a 2021 paper based on an international school in the Netherlands, the results of Roiha and Sommier (2021) differ somewhat from the previous study. Although in-service teachers all reported caring for and 'doing' intercultural education, their discourses on interculturality and diversity were limited to national cultures and traditions in class, with a few of them opening up to more critical views on interculturality beyond mere catalogues of culturalist perspectives, that is, solid and often stereotypical representations of national cultures (see Holliday, 2010).…”
Section: Teachers' Assumptions Beliefs Experiences and Practicescontrasting
confidence: 56%
“…Spain is represented in two publications (Steffen & Bueno-Villaverde, 2018; Bueno-Villaverde et al, 2018). The remaining countries have produced only one publication: The Netherlands (Roiha & Sommier, 2021), the United Kingdom (Ashley-Welbeck & Vlachopoulos, 2020), Canada (Walsh & Casinader, 2019), Uruguay (Bueno-Villaverde et al, 2018), Azerbaijan (Palmer, 2016), Colombia (Lochmiller et al, 2016), France (Lebreton, 2014) and Switzerland (Twigg, 2010). However, it should be noted that some papers sample schools from more than one country, either for comparison or for other methodological or researcher convenience reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Those investigations that include among their objectives knowing aspects related to curriculum design and school organisation have also used the analysis of the different documents that the school has made available (Bueno-Villaverde et al, 2018; O’Boyle, 2009; Karnes & Nugent, 2003). One article uses an ethnographic method for data collection and analysis (Roiha & Sommier, 2021) and another includes graphical representation as a method for obtaining information that would be more difficult to obtain in other ways (Ellingson, 2017) from teacher participants of some dilemmas they have encountered in enquiry processes with students (Twigg, 2010). Although less abundant, there is also some research that uses mixed methods combining both qualitative and quantitative techniques (Walsh & Casinader, 2019; Steffen & Bueno-Villaverde, 2018; Lebreton, 2014) which, as Creswell (2014) points out, allows the most appropriate technique to be selected depending on the objective sought without being limited by the selected methodology.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it could be confirmed that while it is true that diversity in the classroom is an element that could generate mental overload and stress in the teacher, this does not necessarily imply a negative view of the teacher toward diversity in the school. In this sense, a recent study (Roiha & Sommier, 2021) found that although teachers perceive that intercultural education is an important task that they have to implement for a quality education, they usually feel insecure about how to implement it. In this sense, and in connection with our work, we consider that it would an interesting future line of research to consider whether a positive attitude or predisposition of teachers toward diversity could be acting as moderator on the relationship established between perception of attention to diversity and the levels of stress or burnout of teachers in their work in the classroom.…”
Section: Discussionmentioning
confidence: 99%